Silent Scream Book 5 - Harper, Karen (Karen S.) (Ontario, Canada Mira Books, 2018)
"A violent past leads to a present danger... When an old college roommate invites Claire Britten to join her on an archaeological dig at a Florida peat bog, its an offer the renowned forensic psychologist cant refuse. Claires husband, criminal lawyer Nick Markwood, is comforted to see Claire working on a prehistoric burial site instead of an open grave for once. But Claires investigative instincts kick in when some of The Black Bogs perfectly preserved corpses show signs of a grisly fate. What really happened to these people? What started as an exploration of the past soon escalates into an all-too-current danger. Someone is watching--someone who really doesnt want Claire digging into the past or Nick making connections to a current, violent murder case hes investigating. The bogs corpses may be long dead, but if Claire and Nick dont figure out whos gunning for a fresh kill, the next bodies to be discovered will be their own."--
Keywords: Florida -- Fiction; Murder -- Investigation; Fiction; Mystery